Merekonstruksi Pendidikan Islam: Strategi Interdisipliner untuk Menavigasi Kompleksitas Abad ke-21 - Faiq Julia Iqna’a; Misbahul Arifin (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This research focuses on efforts to reconstruct Islamic education through an interdisciplinary approach in response to the complex challenges of the 21st century. The study was conducted at Ma'had Aly Nurul Jadid Probolinggo, a representative institution seeking to integrate traditional Islamic values ​​with contemporary scientific approaches. Using qualitative methods with a single case study design, data were obtained through in-depth interviews, participant observation, and documentation studies with five key informants: leaders, teachers, and students. Data analysis was conducted using the Miles and Huberman model, which encompasses data reduction, data presentation, and drawing and verifying conclusions. The results indicate that the interdisciplinary strategy at Ma'had Aly Nurul Jadid stems from a transformative leadership awareness, cross-disciplinary teacher collaboration, and a shift in the students' learning culture to become more reflective and contextual. The curriculum was developed through a thematic approach that connects Islamic values ​​with everyday life issues. The implications of this research suggest that Islamic education can be renewed without losing its identity by creating a space for epistemological integration rooted in tradition and connected to social reality. These findings reinforce the importance of an interdisciplinary approach as a substantive strategy in the renewal of Islamic education in the modern era.